2014
DOI: 10.2478/pjvs-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary L-arginine intake on the level of antibody titer, the relative organ weight and colon motility in broilers

Abstract: This study was carried out to determine the effect of L-arginine (L-Arg) levels in diet at the starter, grower and finisher phases on immune response, organ development, nitric oxide (NO) metabolism and colon motility in broilers. A total of 500 one-day-old Ross-308 broiler chickens of mixed sex were separated into one Arg-deficient group and four experimental groups. Each group was then divided into five subgroups of 20 birds each. Arginine deficient group for all phases was fed a basal diet which contained 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…110%arginine level had more weight of bursa of Fabricius weight (Bulbul et al, 2014) 25, 50, 75 and 100% Higher spleen weight at higher level of arg. (Cengiz and Kucukersan, 2010) level should be maintained in the diet for optimum performance and immunity in broilers.…”
Section: 100 and 110%mentioning
confidence: 94%
See 4 more Smart Citations
“…110%arginine level had more weight of bursa of Fabricius weight (Bulbul et al, 2014) 25, 50, 75 and 100% Higher spleen weight at higher level of arg. (Cengiz and Kucukersan, 2010) level should be maintained in the diet for optimum performance and immunity in broilers.…”
Section: 100 and 110%mentioning
confidence: 94%
“…Jahanian and Khalifeh-Gholi (2018) reported that increasing the level of arginine 100% in the diet of broilers results in increase in antibodies titer. Similarly, Bulbul et al (2014) reported that the antibody titers of infectious bursal disease (IBD) was more in the grower phase of broiler fed arginine level 110% as compare to NRC recommended level. Levels of arginine influences the weight of internal organs of the broilers which take part in the immunity of broilers (Bulbul et al 2014).…”
Section: Effect Of Arginine On the Growth Performance Of Broilersmentioning
confidence: 98%
See 3 more Smart Citations